The Relationship Between Academic Regulation And Academic Flow In Junior High School Students: Hubungan Antara Regulasi Akademik Dengan Flow Akademik Pada Siswa Sekolah Menengah Pertama - Karinka Aurelia Rahma; Ghozali Rusyid Affandi (Academia Open, 2022)
Students of SMP Negeri 2 Dawarblandong have problems in academic flow, namely students feel unable to concentrate fully and do not enjoy learning and doing math assignments. The purpose of this study was to determine whether there was a relationship between academic self-regulation and academic flow in students of SMP Negeri 2 Dawarblandong in Mathematics. This study uses correlational quantitative methods, the population is all students of SMP Negeri 2 Dawarblandong from grades 7-9 with a total of 510. And the sample is 224 students. The data collection technique used was the academic self-regulation scale with a reliability value of 0.923 and the academic flow scale adapted the flow inventory for students scale with a reliability value of 0.765. The data analysis method uses Spearman's rho correlation with r value = 0.549 and p value = < .001, it can be interpreted that there is a significant relationship between academic self-regulation variables and academic flow. The magnitude of the effect of academic self-regulation on academic flow is quite large (0.549).